Business Education Project: Integrating Learning and Business Projects - Finisica Dwijayati Patrikha; Dwi Yuli Rakhmawati; Veni Rafida; Hapsari Shinta Citra Puspita Dewi (Green Publisher Indonesia, 2024)
This research provides an illustration of a project-based learning experience that combines both understanding and business projects in a Bachelor’s Degree in Business Education program. Specifically, students enrolled in the Marketing Strategy class create a new product (goods or services) and develop an accompanying marketing strategy, including packaging design and marketing videos to be shared on social media. Afterward, students select one product from the show for use in their own semester sales project. In order to assess the effectiveness of this experience, tests were conducted before and after the project using descriptive analysis to analyze the data. Additionally, a questionnaire was distributed to obtain student responses during the classes. The findings demonstrate that Project Based Learning increases students’ abilities to work in groups and individually, and boosts their proficiency in implementing marketing strategies.